2007
DOI: 10.1007/s00453-007-9091-9
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Scheduling on Uniform Parallel Machines with Controllable Job Processing Times

Abstract: In this paper, we provide a unified approach to solving preemptive scheduling problems with uniform parallel machines and controllable processing times. We demonstrate that a single criterion problem of minimizing total compression cost subject to the constraint that all due dates should be met can be formulated in terms of maximizing a linear function over a generalized polymatroid. This justifies applicability of the greedy approach and allows us to develop fast algorithms for solving the problem with arbitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…For problem Q|p(j) = p(j) − x(j), pmtn, C(j) ≤ d|W , it is shown in [22] how to find the actual processing times in O(nm + n log n) time. For the latter problem, Shakhlevich and Strusevich [29] use the SO reasoning to design an algorithm of the same running time and extend it to solving a bicriteria problem Q|p(j) = p(j) − x(j), pmtn| (C max , W ). The best known algorithms for solving problems Q|p(j) = p(j) − x(j), pmtn| (C max , W ) and Q|p(j) = p(j) − x(j), pmtn, C(j) ≤ d|W are discussed in Section 4.2 and in Section 4.3, respectively; their time complexity is O(nm log m) and O(n log n).…”
Section: Scpt Problems With a Common Deadlinementioning
confidence: 99%
See 2 more Smart Citations
“…For problem Q|p(j) = p(j) − x(j), pmtn, C(j) ≤ d|W , it is shown in [22] how to find the actual processing times in O(nm + n log n) time. For the latter problem, Shakhlevich and Strusevich [29] use the SO reasoning to design an algorithm of the same running time and extend it to solving a bicriteria problem Q|p(j) = p(j) − x(j), pmtn| (C max , W ). The best known algorithms for solving problems Q|p(j) = p(j) − x(j), pmtn| (C max , W ) and Q|p(j) = p(j) − x(j), pmtn, C(j) ≤ d|W are discussed in Section 4.2 and in Section 4.3, respectively; their time complexity is O(nm log m) and O(n log n).…”
Section: Scpt Problems With a Common Deadlinementioning
confidence: 99%
“…Such a statement (in different terms) was first formulated in [8] and [10]. For the problems on parallel machines, the corresponding representation of the total processing capacity in the form of a set function is defined in [29]. For all versions of the problem, with a single or parallel machines, the set function ϕ is submodular.…”
Section: Scpt Problems With Distinct Deadlinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shakhlevich and Strusevich [89] have provided a unified approach to solve preemptive scheduling problems with uniform parallel machines and controllable processing times. They demonstrated that a single criterion problem of minimizing total compression cost subject to the constraint that all due dates should be met can be formulated in terms of maximizing a linear function over a generalized polymatriod.…”
Section: Miscellaneous Problem With Preemptive Jobsmentioning
confidence: 99%
“…A systematic development of a general framework for solving scheduling problems with controllable processing times via submodular methods has been initiated by Shakhlevich and Strusevich [14,15] and further advanced by Shakhlevich et al [16] and Shioura et al [17]. This paper makes an additional contribution to the development of this approach.…”
Section: Introductionmentioning
confidence: 95%